New Drugs and Strategies for Management of Clostridium difficile Colitis. (July 2014) - Higa, J. T.; Kelly, C. P.
Approaches for management of Clostridium difficile infection continually evolve as research reveals shifts in epidemiology, microbial pathogenesis, disease severity states, and response to therapy. These new discoveries significantly impact diagnostic and therapeutic strategies, given the high morbidity associated with this common nosocomial infectious diarrhea. Critically ill patients are at an increased risk of developing diarrheal illness like C. difficile and succumbing to potentially fatal complications of this infection. Early diagnosis of severe disease state may improve patient outcomes. In this article, we review treatment strategies and new approaches for the management of C. difficile in critically ill patients.